That's What Friends Are For: Hospitality and affective bonds fostering collective empowerment in an intentional community. Issue 5 (May 2017) - Farias, Carine
Processes of collective empowerment are essentially concerned with the production of social and emotional configurations fostering a mutual awareness that social change is both desirable and feasible. Using an ethnographic study of an intentional community of activists, this paper analyses how friendship practices produce enduring forms of empowerment based on democratic praxis. The analysis shows that nurturing affective bonds of friendship facilitates the prefiguration of alternative ways of life through the experience of living together. This is supported by the cultivation of hexis as a political frame, which reassesses the centrality of human beings' otherness and fosters complex equality within relationships.